Adding action to the interview: Conceptualizing an interview approach inspired by action research elements. Issue 1 (March 2016) - Nielsen, Helle; Lyhne, Ivar
Inspired by action research traditions, this article argues for a need to strengthen the role of interviews as an arena for generating action through mutual reflection. The aim is to point out and conceptualize the unarticulated action-oriented elements that appear in action researchers' interview practice. The article traces the development of the interview from hermeneutic toward critical utopian action research in order to identify core action-oriented elements of the interview. These elements are empirically studied in two cases of interview practices in research projects. Based on the findings, we outline elements of the action-oriented approach for doing interviews. The related ethical and practical implications are discussed and further research is outlined.